Studi Kelayakan Pabrik Dodecylbenzene Sulfonic Acid dari Sulfur Dioksida Pada Gas Buang PLTU - At Taufiq, Putri Zahra; Nursanto, Eduardus Budi (Prosiding Seminar Nasional Teknoka, 2025)
The increase in population is directly proportional to the demand for energy. Fossil fuels serve as the main energy source in various industries, including electricity generation through PLTU (Steam Power Plant). These plants produce flue gases containing various components, among which sulfur dioxide (SO2) is a major pollutant whose concentration is strictly regulated. Utilizing SO2 as a raw material for producing Dodecylbenzene Sulfonoc Acid – a surfactant compound – can reduce SO2 emissions from PLTU by up ti 98%. The feasibility of this plant was assessed through a techno-economic study using ROI (Return of Investment), POT (Pay Out Time), and BEP (Break Even Point) analyses. The results indicate an ROI of 35.18%, a POT of 2.18 years, and a BEP of 15.76%, demostrating that the proposed plant is economically feasible to establish.